Periodontal Practice and Referral of Patients by General Dental Practitioners in Province No.1 Nepal - Acharya, Pujan; Gautam, Ujwal (Birat Journal of Health Sciences, 2023)
Introduction: General dental practitioners and periodontists working in a close alliance is considered to bestow effective outcome in the context of diagnosis and management of periodontal diseases. Recently, general practitioners are inclined to render the majority of non-surgical procedures by themselves and avoid surgical part. This obscures functional as well as esthetic demand contributing to periodontally challenged conditions. In advanced stages, no matter how efficiently a skilled periodontist handles the case, redemption is not possible. Objectives: To assess the periodontal practice and referral of patients by general dental practitioners to periodontists. Methodology: An online survey using Google Forms was conducted among the general dental practitioners working in private clinics in province no.1, Nepal from November 2021 to January 2022. A total of 64 general dental practitioners were surveyed using a self-administered questionnaire. Descriptive statistics were calculated. Results: The response rate for the present study was 51.2% out of which only 17.2% referred patients to periodontists for non-surgical periodontal therapy and scaling was the most performed procedure by all the practitioners themselves. However, 92.2% referred patients to periodontists for surgical procedures and a majority of the referrals were for mucogingival surgeries. Majority of them expressed satisfaction regarding the number of continuing dental education programs being conducted despite minimum participation. Conclusion: Majority of the general dental practitioners seemed to perform non-surgical periodontal therapy by themselves while considering referral for surgical interventions. Also, minimum participation despite remarkable satisfaction in the conduction of continuing education programmes calls for a need to explore the inadequacy.